A Review Paper on Solar Energy Stored Cooker and its Use (International Journal of Innovative Research in Engineering & Management, 2021)
Solar cooking is popular in India and many other developing  nations where LPG, coal, and other fossil fuels are scarce. A  solar cooking system with or without temporary heat storage  has been designed and deployed in a number of nations across  the globe. Cooking necessitates the use of thermal energy,  which is presently supplied by liquefied petroleum gas,  kerosene, and coal, all of which are costly fuels. As a source of  heat, solar energy may also be utilized to prepare food. Solar  energy is accessible nearly everywhere. To effectively prepare  meals, a solar energy-stored cooker is utilized. The solar energy  storage cooker is intended for both cooking and storing thermal  energy. When heat energy is stored, the oven's efficiency and  utility are improved when sunshine is not available. This kind  of cooking oven is long-lasting, low-cost, and effective, making  it suitable for every household. This article provides an in-depth  examination of the solar energy storage cooker and how it may  be used in today's society. Despite the fact that many studies in  this area have been performed in the past, additional study in  this field is urgently needed in the future.
Keywords: Energy; Heat Storage; Solar Cooker; Solar radiations; Sun